Quadrotor Convergence Trajectory Optimization Model Based on Minimum Energy Consumption (Advances in Applied Mathematics and Mechanics, 2018)
Energy consumption is an important challenge to planning path of quadrotor and the energy-calculating of quadrotor flight trajecotry is not yet fully completed. This paper mainly researches on optimizing the convergence trajectory of the quadrotor on energy-saving. Firstly, the equivalence between the lift angular accelerated function and the flight trajectory function is proved. Then, the energy-calculating formula of quadrotor flight trajectory is obtained by using the relationship between lift and voltage. Furthermore, the quadrotor convergence trajectory model is established with the goal of minimum energy consumption. Finally, through the numerical simulation, the optimized convergence trajectories under different boundary conditions are obtained. Moreover, the specific flight position in real time can be got and implemented into the real-time flight trajectory planning.